Local uniqueness of m-bubbling sequences for the Gel'fand equation. Issue 6 (3rd June 2019) - Bartolucci, Daniele; Jevnikar, Aleks; Lee, Youngae; Yang, Wen
Abstract: We consider the Gel'fand problem, { Δ w ε + ε 2 h e w ε = 0   in   Ω, w ε = 0   on   ∂ Ω, where h is a nonnegative function in Ω ⊂ R 2 . Under suitable assumptions on h and Ω, we prove the local uniqueness of m − bubbling solutions for any ε > 0 small enough.